Effects of salt on colour degradation kinetics of visual green colour in fluted pumpkin (telfairia occidentalis) leaves (2011)
The effect of common salt (0, 1, and 2% by weight) on visual green colour degradation of fluted pumpkin (Telfairia occidentalis) puree over a temperature range of 50–100° C was studied. Hunter colour scale values L (lightness), a (greenness or redness) and b (blueness or yellowness) of each treated samples were measured. The visual colour was evaluated using a Hunter lab colorimeter in terms of L, a and b. The results were analysed using Oakdale Engineering Datafit 8.2. The degradation of visual green colour of fluted pumpkin increased with an increase in heat treatment time and salt concentration. The degradation as measured by -a value followed a first order kinetics. There was consistent decrease in L and -a values with an increase in treatment time and temperature. During heat processing, the puree turned olive green and the a value changed from an initial value of -11.32 to -10.40, -10.73 and -10.87 at 50°C for the 0, 1 and 2% level of salt addition, respectively. The corresponding values at 100°C were -3.11, -3.65 and -3.72, respectively. There is stabilization of green colour in thermally processed fluted pumpkin puree containing salt which decreases the rate of chlorophyll degradation. The stabilizing effect of salt is not well established and no information is available on fluted pumpkin leaves, especially in term of visual colour. The paper established the stabilizing effect of salt on fluted pumpkin leaves and modelled the degradation kinetics with Arrhenius equation.